2022
DOI: 10.3390/ph15060720
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between the Actions of Glucagon-like Peptide-1 Receptor Ligands in the Protection of the Heart against Ischemia Reperfusion Injury

Abstract: Tirzepatide is a dual glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) receptor agonist and a promising therapy for type 2 diabetes mellitus (T2DM). GLP-1 is an incretin hormone with therapeutic potential beyond type 2 diabetes mellitus. However, GLP-1 is rapidly degraded by dipeptdyl peptidase-IV (DPP-IV) to GLP-1 (9-36). Exendin-4 (Ex-4) is a DPP-IV-resistant GLP-1 receptor agonist which, when truncated to Ex-4 (9-39), acts as a GLP-1 receptor antagonist. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Anesthesia was performed with intraperitoneal injections of sodium pentobarbital (60 mg/kg) and the animals were anticoagulated by heparin (1000 U/kg). Heart mounting cannulation and perfusion were done as described previously [ 59 , 60 ]. Briefly, isolated heart was reversely perfused with a freshly prepared Krebs–Hensleit (KH) buffer, pH 7.35 to 7.45 at 37.0 ± 0.5 °C and was gassed with CO 2 (5%) and O 2 (95%).…”
Section: Methodsmentioning
confidence: 99%
“…Anesthesia was performed with intraperitoneal injections of sodium pentobarbital (60 mg/kg) and the animals were anticoagulated by heparin (1000 U/kg). Heart mounting cannulation and perfusion were done as described previously [ 59 , 60 ]. Briefly, isolated heart was reversely perfused with a freshly prepared Krebs–Hensleit (KH) buffer, pH 7.35 to 7.45 at 37.0 ± 0.5 °C and was gassed with CO 2 (5%) and O 2 (95%).…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after the isolation process, the heart was cannulated to a modified Langendorff system, as described previously [49,50]. To fix the heart to the modified Langendorff system, a cannula was inserted in the aorta and was stabilized by a small clip.…”
Section: Methodsmentioning
confidence: 99%
“…The GLP1R antagonist exendin (9-39) eliminated the cardioprotective effect of exendin-4 but did not affect the cardioprotective effect of GLP-1(9-36) [42]. It was concluded that the protective effect of exendin-4 is accompanied by the activation of the GLP1R, and the protective effect of GLP-1(9-36) does not depend on stimulation of this receptor [42]. CAO (30 min) and reperfusion were carried out in rats [43].…”
Section: The Infarct-reducing Effect Of Glp1r Agonistsmentioning
confidence: 99%
“…Isolated rat hearts were exposed to regional ischemia (30 min) and reperfusion (30 min) [42]. The hearts were perfused with a solution containing exendin-4 (100 nmol/L) or GLP-1(9-36) (100 nmol/L) 5 min before reperfusion and perfusion was continued for 10 min of reperfusion.…”
Section: The Infarct-reducing Effect Of Glp1r Agonistsmentioning
confidence: 99%